Effect of processing parameters on bond properties and microstructure evolution in ultrasonic additive manufacturing (UAM). (8th March 2021) - Li, Peng; Wang, Zhenqiang; Diao, Mingxia; Guo, Chunhuan; Wang, Jiandong; Zhao, Chengzhi; Jiang, Fengchun
Abstract: Ultrasonic additive manufacturing (UAM) is an advanced additive manufacturing technique that utilizes ultrasonic energy to rapidly joining thin metal tapes into solid parts in a layer accumulating manner. In this study, the effects of processing parameters on the bond properties of UAM samples were investigated via peel tests, linear weld density (LWD) measurements, microhardness tests and EBSD. The results reveal that, in terms of the overall tendency, the peeling strength and LWD increase with the increasing amplitude and normal force settings. However, a parameter threshold phenomenon and two different mechanisms that affect the bond properties were also observed. Furthermore, the microstructure evolution results show that the development of the interface is closely related to the applied parameters, which can also well explain the bond property variations and the parameter threshold phenomenon.